The impact of day care attendance on antibiotic use among children aged 0–12 years: A population-based register study - Räsänen, Tapio; Saarikallio-Torp, Miia; Rättö, Hanna; Kari, Heini (PLOS, 2026)
Day care attendance is known to be an important source of infection transmission in children. Having older siblings has also been shown to increase the risk of recurrent infections. We use comprehensive register data to study if the cumulative antibiotic use in children differs according to the duration of how long the child has been in home care before entering day care. The study focuses on children born in Finland between 2000 and 2005, with follow-up until age 12. Children are linked to their biological parents, and the analysis includes control variables such as mother’s age and education level. In addition to descriptive evidence, we employ statistical models to study the association between the duration of home care and antibiotic exposure. The results show that almost all children were exposed to prescribed antibiotics within the first 12 years of their life. One fifth of the children had more than 15 antibiotic purchases by the age of 12. Four most commonly prescribed antibiotics were amoxicillin, azithromycin, cefalexin, and amoxicillin with beta-lactamase inhibitor. The results from Poisson regression model affirmed that cumulative use was lower in children with longer home care duration. Regardless of the number siblings, the number of cumulative antibiotic purchases remained lowest in the group of children with the longest home care period, and the results remained robust after controlling for the mother’s age and education, and immigrant background. These findings contribute to a broader understanding of how early childhood care arrangements may be associated with long-term patterns of antibiotic use, with potential relevance for public health planning and antimicrobial stewardship.